Lichenized fungi (Ascomycota) from Dupkata Reserve (Rhodopi Mts, Bulgaria): Lichenized fungi in Dupkata Reserve (Rhodopi Mts) - Stoykov, Dimitar Yordanov (Journal of BioScience and Biotechnology, 2025)
Results from the study on lichens in the Dupkata protected area, Rhodopi Mts are presented. Fifty-one species of lichen-forming fungi were reported for the first time from the Reserve. Among them, Arthopyrenia analepta s.l. and Lecanora argentata were new records from the Rhodopi Mts. Data on some rarely recorded and less common species in Bulgaria were briefly discussed.